PEMANFAATAN ENERGI ANGIN COOLING TOWER SEBAGAI SUMBER ENERGI ALTERNATIF DI AREA PAINTING PT ASTRA DAIHATSU MOTOR KARAWANG - Nugraha, Afitro Adam; Lukman Wijanarno; Ajib Rosadi; Hadiyanto (LPPM Politeknik Astra, 2024)
The global energy crisis which is based on fossil-based energy security encourages efforts to make a just and sustainable energy transition. This study aims to explore and test the potential utilization of wind energy sources from Cooling Towers as an efficient and sustainable alternative energy source. Cooling Tower at PT Astra Daihatsu Motor is the focus of research because this company has implemented the Sustainable Development Goal's (SDG's) program which is in line with the goal of contributing to handling global problems, including in clean energy and tackling climate change. Wind energy from the Cooling Tower is analyzed using the wind power formula which produces a power of 1,373 watts at an average wind speed of 9 m/s from 1 hole in the Cooling Tower. To optimize its utilization, a HAWT (Horizontal Axis Wind Turbine) type wind turbine is installed in the Cooling Tower chimney. This turbine produces 425 watts of wind power with a power coefficient of 0.43 and a tip speed ratio of 9.7. PMSG (Permanent Magnet Synchronous Generator) type generator was chosen as a converter of kinetic energy into electrical energy. The implementation results show that the wind turbine can only produce 79.52 watts with a generator efficiency of 18.7% of the received wind resources. This research obtained electricity cost savings of Rp. 660,660/year and reduce TCO2 emissions by 0,416 TCO2/tahun. Utilization of wind energy sources from Cooling Towers shows potential as a sustainable alternative energy source. In addition to reducing dependence on fossil energy sources, the use of wind energy also has a positive impact on the environment by reducing greenhouse gas emissions.